Analysis of the Influence of Regional Taxes and Levies on Regional Original Income Through Economic Growth Case Study Tanjung Balai Area - Rambe, Dhea Nita Syafina; Syafii, M. (Neraca Keuangan : Jurnal Ilmiah Akuntansi dan Keuangan, 2025)
The purpose of this study is to determine the effect of Regional Taxes and Regional Levies on Economic Growth in Tanjung Balai. The data used in this study are secondary data from the Central Statistics Agency (BPS), the data used is data for the period 2010 - 2024. The analysis method used in this study is the multiple linear regression analysis method using statistical tests by determining a 95% confidence level (α = 0.05) in the t-test. The results of this study indicate that partially the Regional Tax variable has a positive and significant effect on Economic Growth and Regional Levies have a positive and significant effect on Economic Growth. Then simultaneously Regional Taxes and Regional Levies have a positive and significant effect on Economic Growth.